Menjembatani Etika dan Komitmen: Peran Mediasi Nilai-Nilai Kerja Islami dalam Perbankan Syariah - Nurlaila Nurlaila; Sri Langgeng Ratnasari; Meirani Harsasi; Zulkifli Sultan (Society, 2025)
This study investigates the influence of personality, competence, and performance on organizational commitment in Islamic banks, with Islamic Work Ethics (IWE) serving as a mediating variable. Conducted in North Maluku, Indonesia, the research employs a quantitative explanatory design and utilizes structural equation modeling (SEM) with AMOS 24.0 to test the proposed relationships. Data were obtained through closed-ended questionnaires distributed to 175 employees selected via probability sampling across several Islamic banking institutions. The findings reveal that personality and performance have a significant positive effect on organizational commitment, whereas competence does not exert a direct influence. Furthermore, IWE significantly contributes to strengthening organizational commitment by embedding ethical values into workplace behavior. Personality and competence both positively affect the application of IWE, which in turn mediates their relationship with organizational commitment. These results underscore the strategic importance of fostering competence through conflict management training, enhancing the internalization of Islamic ethical principles, and promoting innovation in service delivery.